The Geological Heritage of Ñandeyvytykuera Geopark Project in Paraguay - Néstor Damian Salinas Franco; Romina Mariel Celabe Gaona; Diego Adán López (Geoconservation Research)
Paraguay's first geopark began in 2017 and work is ongoing. The project is managed by a committee comprised of key stakeholders from state and municipal entities, universities, and local communities, to promote and generate sustainable local development strategies. Paraguay has significant geodiversity, particularly in the eastern region, with rocks ranging from the Paleoproterozoic to Quaternary sediments. Appreciation of this extensive geodiversity only began a decade ago with a focus on heritage value and preservation of certain geological sites. The methodology presented here involves a qualitative inventory of geosites and geodiversity sites (GS) with scientific, educational, and tourist value. Additionally, it considers their fragility and vulnerability within the territory of the Geoparque ÑandeYvytykuera, covering the departments of Central, Cordillera, and Paraguarí. The GS with the highest scientific value is the columnar sandstones of Cerro Koi. Those with superior educational qualities include the GS Ñemby Hill, Perõ Hill, and Yaguarón Hill. Tourism value is highest at the GS San Bernardino Beach. As for fragility and vulnerability, the Itauguá Fossiliferous Shales GS stands out due to the deterioration and loss of its geodiversity, attributed to a diverse array of unique marine fossils. In conclusion, we recommend adding more locations as a geoconservation strategy, and expanding studies that incorporate quantitative methodologies to provide more precise data and further these and other investigations.